Faktor-Faktor yang Mempengaruhi Kepuasan Pasien terhadap Pelayanan Kesehatan: Narrative Literature Review: Factors Influencing Patient Satisfaction with Healthcare Services: A Narrative Literature Review - Dewi Agustina; Fitri Annisa; Nabilla Suci Ramadhani; Fazri Khoirunnisa Purba; Rintan Arzeti; Risna Utami; Alya Najwa; Riska Rahmadianti; Adelia Putri Maharani; Unaisah Annufaisah Nuh Siregar; Azzahra Sabrina Nasution (MPI Press, 2026)
Introduction: Patient satisfaction is a critical indicator in evaluating healthcare service quality, reflecting the extent to which patient expectations are met by actual service experiences. Factors such as healthcare worker communication quality, facility adequacy, staff responsiveness, and empathy significantly influence patient perceptions. Objectives: To comprehensively examine factors influencing patient satisfaction with healthcare services by integrating the SERVQUAL model and Disconfirmation Theory. Methods: A narrative literature review was conducted searching Google Scholar, PubMed, Garuda, and SINTA databases. Articles published between 2020–2026 were screened; 12 articles met inclusion criteria and were analyzed using a thematic narrative approach. Results: All five SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, empathy) consistently related to patient satisfaction levels. Responsiveness and empathy were identified as dominant factors. Disconfirmation Theory confirms that satisfaction is formed through the gap between patient expectations and actual service experiences. Conclusion: Improving healthcare service quality (particularly responsiveness and empathy) is a key strategy for enhancing patient satisfaction. Integrating SERVQUAL and Disconfirmation Theory offers a more comprehensive analytical framework for understanding patient satisfaction.